2016
DOI: 10.1002/1873-3468.12130
|View full text |Cite
|
Sign up to set email alerts
|

Violaxanthin inhibits nonphotochemical quenching in light‐harvesting antenna of Chromera velia

Abstract: Edited by Richard CogdellNon-photochemical quenching (NPQ) is a photoprotective mechanism in light-harvesting antennae. NPQ is triggered by chloroplast thylakoid lumen acidification and is accompanied by violaxanthin de-epoxidation to zeaxanthin, which further stimulates NPQ. In the present study, we show that violaxanthin can act in the opposite direction to zeaxanthin because an increase in the concentration of violaxanthin reduced NPQ in the light-harvesting antennae of Chromera velia. The correlation overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Janssen and Rhiel , Kereiche et al ) than in higher plants, as previously also found for other red clade species in general (see, e.g. Büchel , Kaňa et al ). On the other hand, it may relate to the fact that chlorophyll c ‐containing antennas seem to be more delicate (see, i.e.…”
Section: Discussionsupporting
confidence: 75%
“…Janssen and Rhiel , Kereiche et al ) than in higher plants, as previously also found for other red clade species in general (see, e.g. Büchel , Kaňa et al ). On the other hand, it may relate to the fact that chlorophyll c ‐containing antennas seem to be more delicate (see, i.e.…”
Section: Discussionsupporting
confidence: 75%
“…We also observed a significant decrease in the chlorophyllto-carotenoid ratio in Rieske FeS ox plants, which would suggest that there is a greater investment in photoprotection relative to the increased chlorophyll for light harvesting. This increase in carotenoids relative to chlorophyll may contribute to the lower NPQ observed in Rieske FeS ox plants (Kaňa et al, 2016). Lutein, neoxanthin, and violaxanthin are the main xanthophyll pigment constituents of the largest lightharvesting pigment-protein complex of photosystem II (FW).…”
Section: Overexpression Of Rieske Fes Significantly Modifies the Pigmmentioning
confidence: 99%
“…Finally, a direct protonation of pigment-proteins has been observed in vitro (Ruban et al, 1994; Walters et al, 1996; Kaňa et al, 2012b; Xiao et al, 2012; Belgio et al, 2013). The qE sensitivity to luminal protons is controlled by various allosteric regulators (see the details of the concept in Ruban et al, 2012) including xanthophylls (e.g., zeaxanthin, and violaxanthin Niyogi et al, 1998; Kaňa et al, 2016) and the PsbS protein (see e.g., Li et al, 2000; Johnson and Ruban, 2010). …”
Section: Regulatory Role Of Protons and Ions In Triggering Non-photocmentioning
confidence: 99%